THE REASONS FOR IMPLEMENTING THE DIVERSIFICATION STRATEGY DEVELOPED THROUGH AGROINDUSTRY ON SMALL RURAL PROPERTIES - Sobczuk, Daiane Aline Tomaz; Bertolini, Geysler Rogis Flor (Revista Econômica do Nordeste, 2025)
The general objective of this research is to analyze the reasons for implementing the diversification strategy developed through agroindustry in small rural properties in the municipality of Medianeira-PR. The research was carried out through a qualitative, descriptive and exploratory multi-case study, based on structured interviews carried out between January and April 2022. The field of study is the family properties that diversify their production through of the family agroindustry. As the main findings of the research, it was identified that, in the implementation of the rural livelihood diversification strategy, the effective motivation revolves around income generation, staying in rural areas and the opportunity to have a better quality of life. Producers also strategically seek to add new knowledge to family traditions in order to create new products and services that are reverted through customer satisfaction. Finally, the performance of the livelihood diversification strategy through agroindustry shows that access to natural, human, social, physical and financial capital is essential for the development of small family agroindustries, in addition to the fact that the knowledge acquired by families improves the business and diversification strategy promotes sustenance; consequently, families and their successors remain on rural properties.